2014
DOI: 10.1002/mbo3.186
|View full text |Cite
|
Sign up to set email alerts
|

All subtypes of the Pmp adhesin family are implicated in chlamydial virulence and show species‐specific function

Abstract: The bacterial pathogens Chlamydia trachomatis and C. pneumoniae are obligate intracellular parasites, cause a number of serious diseases, and can infect various cell types in humans. Chlamydial infections are probably initiated by binding of the bacterial outer membrane protein OmcB to host cell glycosaminoglycans (GAGs). Here, we show that all nine members of the polymorphic membrane protein (Pmp) family of C. trachomatis mediate adhesion to human epithelial and endothelial cells. Importantly, exposure of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 51 publications
(158 reference statements)
3
84
0
1
Order By: Relevance
“…Chlamydiae enter cells via multiple routes, using mechanisms that are poorly understood (49). In previous studies we identified the Pmp proteins of C. pneumoniae and C. trachomatis as adhesins that are essential for the successful infection of human cells (22,27). Pmps are known to share characteristic features with Type V autotransporters, including proteolytic processing (13,14,16,18,22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chlamydiae enter cells via multiple routes, using mechanisms that are poorly understood (49). In previous studies we identified the Pmp proteins of C. pneumoniae and C. trachomatis as adhesins that are essential for the successful infection of human cells (22,27). Pmps are known to share characteristic features with Type V autotransporters, including proteolytic processing (13,14,16,18,22).…”
Section: Discussionmentioning
confidence: 99%
“…Adhere to Human Cells-In previous studies, Pmp6, -20, and -21 from C. pneumoniae and all nine Pmps from C. trachomatis serovar E, were characterized as bacterial adhesins that are important for the infection of human epithelial cells (22,27). The motifs GGA(I/L/V) and FXXN are characteristic for Pmps and essential for adhesion (22).…”
Section: Fxxn-induced Oligomerization Of Pmp21-d Is Crucial For Its Amentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple putative chlamydial factors, such as the major outer membrane protein (MOMP) (10)(11)(12)(13), outer membrane complex (OMC) protein B (OmcB) (14)(15)(16), and the polymorphic membrane proteins (Pmps) (17)(18)(19), and host-derived factors, such as heparin sulfate (16,20), epidermal growth factor receptor (EGFR) (21), estrogen receptor (22), and insulin-like growth factor 2 receptor (23), have been proposed to mediate chlamydial interactions with host cells. However, the precise structural basis of the interactions between an EB and a host cell during chlamydial infection in animals and humans remains ill defined.…”
mentioning
confidence: 99%